Mobilidade urbana e a frequentação do centro principal de Presidente Prudente - SP - Cruz, Marcos Paulo de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
With the increasing diversity in urban spaces, daily life has become more and more complex and, therefore, it starts to assure to the collective coexistence an immeasurable gain in experiences and ideas. Aiming to contribute to the advancement of studies of cities, this research report aims to understand aspects of the frequentation of the main center of Presidente Prudente - SP. Through explorations based on data collected in surveys with questions involving the frequency and purpose of attendance, the alternatives in locomotion, and the recognition of the center, our work is supported by a quantitative analysis, and from it we raise reflections that contribute to the understanding of the reproduction of urban life in a medium-sized city context.

Com a crescente diversidade nos espaços urbanos a vida cotidiana vem se tornando cada vez mais complexa e, portanto, passa a assegurar ao convívio coletivo um ganho imensurável em experiências e ideias. Ambicionando contribuir ao avanço dos estudos das cidades, o presente relatório de pesquisa tem como finalidade perceber aspectos da frequentação do centro principal de Presidente Prudente - SP. Mediante explorações a partir de dados coletados em enquetes com indagações envolvendo frequência e finalidade de frequentação, alternativas em locomoção, e o reconhecimento do centro, nosso trabalho se ampara em uma análise quantitativa, e, a partir dela levantamos reflexões que contribuem ao entendimento da reprodução da vida urbana num contexto de cidade média.
Urban mobility and the attendance of the main center of Presidente Prudente - SP
Keywords: Urban mobility; Intra-urban centrality; Medium-sized cities; Mobilidade urbana; Centralidade intraurbana; Cidades médias; Presidente Prudente